Anticipatory Inhibition of EMG Activity of the Human M. Soleus at Voluntary Contraction of Its Antagonists - Slivko, E. I.; Ivanchenko, Ye. Z.; Mikaelyan, G. R.; Panchenko, M. A.; Сливко, Емануіл Ілліч; Іванченко, Олена Зенонівна; Мікаєлян, Геннадій Ромеович (My University, 2018)
Quantitative changes in background tonic EMG activity of m. soleus within a premotor period of voluntary contraction of its antagonists were examined in healthy humans. The above activity was recorded in the lying position at voluntary moderate tonic tension of this muscle and in the upright position, where the body was supported by both legs. The effect of voluntary flexion of the ipsilateral ankle joint (a simple motor reaction to a light signal) was examined. It was found that the intensity of soleus EMG in both tested positions, began to decrease 30–60 msec before the appearance of EMG activity recorded from the ankle flexor m. tibialis anterior, and such inhibition reached the maximum at the end of the premotor period. The observed dynamics of tonic EMG in the m. soleus show that an anticipatory drop in the activity of soleus motoneurons develops before the beginning of voluntary movements. Possible physiological mechanisms underlying this phenomenon are discussed. We believe that, within the premotor period, impulsation coming via mostly the corticospinal tract to soleus motoneurons decreases due to the action of central motor commands, and this leads to lowering of tonic tension of this muscle.
Keywords: electromyography; m. soleus; m. tibialis anterior; voluntary movement; premotor period; reciprocal inhibition